Ezekiel 29.6b–7 and metaphorical uses of canes in the Hebrew Bible - Schipper, Jeremy (Journal for the study of the Old Testament, 2025)
This article argues that Ezekiel 29.6b–7 reflects an underappreciated metaphorical depiction of a cane, and that we can find metaphors involving canes elsewhere in the Hebrew Bible with Ezek. 29.6b–7 containing the most explicit example. These metaphors can be used to articulate warnings about the unreliability of alleged allies as well as the reliability of Yahweh. Other metaphors for God in the Hebrew Bible may be more familiar, but the metaphor discussed in this article suggests the need for further attention not only to the textual metaphorization of injured or disabled bodies but also to the objects that people with injuries or disabilities would have used to support themselves in the ancient world.